1998
DOI: 10.3354/ame015191
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of oxygen respiration, nitrogen mineralization, and nitrification in Arctic sediments

Abstract: The temperature dependence of oxic minerahzation processes in perenn~ally cold coastal sediments from Arctic Svalbard, Norway, was determined in short-term incubations at -1 to 44'C and compared to similar incubations with warm temperate sediment. For oxygen respirat~on, nitrogen mineralization, and nitrification, adaptations to low temperature were evident with the microbial comrnunities from Svalbard. Oxygen respiration rates showed the same temperature dependence at all sites around Svalbard, with relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
83
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 16 publications
14
83
0
Order By: Relevance
“…This has been demonstrated with Nitrosospira strains grown in pure culture [47] and with AOB communities from different soils [48]. If these observations are generalizable and there is minimal functional redundancy between taxa (i.e., phylogenetically distinct communities have distinct temperature sensitivities), it may explain why the temperature responses in nitrification activity can vary so widely across different soils [49,50] or sediment samples [51]. More broadly, if distinct AOB communities do indeed have different temperature responses, it would suggest that information on the spatial variability in AOB communities could be integrated into models of soil nitrogen dynamics in order to better predict how soil nitrogen dynamics may be affected by changes in climatic conditions.…”
Section: Factors Correlated With the Observed Patterns In Aob Biogeogmentioning
confidence: 83%
“…This has been demonstrated with Nitrosospira strains grown in pure culture [47] and with AOB communities from different soils [48]. If these observations are generalizable and there is minimal functional redundancy between taxa (i.e., phylogenetically distinct communities have distinct temperature sensitivities), it may explain why the temperature responses in nitrification activity can vary so widely across different soils [49,50] or sediment samples [51]. More broadly, if distinct AOB communities do indeed have different temperature responses, it would suggest that information on the spatial variability in AOB communities could be integrated into models of soil nitrogen dynamics in order to better predict how soil nitrogen dynamics may be affected by changes in climatic conditions.…”
Section: Factors Correlated With the Observed Patterns In Aob Biogeogmentioning
confidence: 83%
“…Such studies have shown an insignificant difference in temperature adaptation of aerobic respiration between arctic and temperate communities (Thamdrup & Fleischer 1998). In contrast, lower Q 10 values have been reported for benthic sulphate reduction in Antarctic sediments compared to measurements performed at temperate latitudes (Isaksen & Jørgensen 1996).…”
Section: Introductionmentioning
confidence: 89%
“…A comparative study on short-term temperature effects of aerobic respiration in slurred coastal sediments also concluded that Arctic and temperate sediments had similar Q 10 values (Thamdrup & Fleischer 1998). However, a seasonal temperature acclimation was observed for the temperate site, with Q 10 (0-10°C) of 2.0 and 3.0 for winter (1 to 3°C) and summer (13 to 15°C), respectively .…”
Section: Heterotrophic Temperature Responsementioning
confidence: 99%
See 2 more Smart Citations